Pariwisata Olahraga Paralayang sebagai Pendukung Minat Wisatawan di Bukit Kekep Kabupaten Wonosobo - Wildan, Muhamad; Yuwono, Cahyo (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the strategies, processes, and constraints of online physical education, sports and health at SD Negeri 03 Tanjung, Kedungtuban District, Blora Regency using a qualitative research approach with descriptive results. The research procedures are as follows: observation, interviews, questionnaires and documentation. The results of the research show that the strategy for learning physical education for elementary schools during a pandemic is elementary school SD Negeri 03 Tanjung, Kedungtuban District, Blora Regency during the Covid 19 pandemic, elementary school physical education teachers planned and the learning process during the pandemic was carried out online.. constraints on the online learning process included sports-related infrastructure and internet networks. The conclusion from the research results is as follows: learning during Covid-19 continues, with adjustments to the Ministry of Education and Culture regulations. Processes related to learning include planning, process, and evaluation of learning. the obstacles experienced in online learning are related to online learning supporting facilities and infrastructure, class conditioning, and student learning motivation.